Effect of moisture content on physical properties of aged okra (Abelmoschus esculentus) seeds - MANOJ KUMAR MAHAWAR; D.V.K. SAMUEL; J.P. SINHA; S.K. JAIN; S.K. JHA; K.K. TYAGI (Seed Research, 2026)
This particular research investigation was conducted to determine selected moisture dependent physical properties of okra seed lots. Three different okra seeds lots based on their moisture content (10.98 to 16.89% d.b) and germination (80 to 50%) was chosen in this study. Average geometrical mean diameter and sphericity were in the range of 4.731 to 5.019 mm and 0.896 to 0.914, respectively. Bulk density and true density decreased from 0.622 to 0.604 g/cm³ and 1.138 to 1.126 g/cm³ respectively with the increase in moisture content from 10.98 to 16.89% d.b. Porosity and angle of repose was found increasing from 45.34 to 46.35% and 24 to 29°, respectively with moisture content. Coefficient of static friction (plywood, mild steel and cast iron) increased linearly with moisture content from 0.3979 to 0.4327, 0.3878 to 0.4203 and 0.362 to 0.3959, respectively for all the three materials used. Mean peak compressive force decreased linearly from 93.70 to 81.72 N with the increase in moisture content. Terminal velocity was positively correlated with moisture content and increased from 9.2 to 9.8 m/s for the different seed lots. Outcome of this particular study were found supportive in designing seed priming prototype suitable for priming purpose of selected vegetable seeds.